Effect of homeopathic medicines on the germination and initial growth of Salicornia bigelovii (Torr.) - Mazón-Suástegui, José Manuel; Ojeda-Silvera, Carlos Michel; Agüero-Fernández, Yuneisy Milagro; Batista-Sánchez, Daulemys; Batista-Sánchez, Dailenys; García-Bernal, Milagro; Abasolo-Pacheco, Fernando (REVISTA TERRA LATINOAMERICANA, 2020)
The effect of homeopathic medicines on germination and initial growth of Salicornia bigelovii (Torr.) was evaluated under controlled conditions. A completely randomized experimental design was applied with three homeopathic treatments, Natrum muriaticum 7CH (NaM-7CH); Phosphoricum acidum 13CH (PhA-13CH); Natrum muriaticum 31CH (NaM-31CH); distilled water as control (AD) and six replicates per treatment. The response variables were the percentage and germination rate, stem and radicle length, and fresh and dry biomass of aerial and radicle parts. An analysis of variance and subsequent tests were performed to compare means (Tukey HSD, P ≤ 0.05) when a significant difference between treatments was found. A significant increase was observed in all the response variables evaluated in all the homeopathic treatments with respect to control (AD). The variables with the highest response were germination percentage, with values up to 44% and stem and radicle length with 35% above the control treatment in plants treated with NaM-7CH. These results confirmed the positive effect of homeopathic medicines on germination and initial growth of S. bigelovii, revealing that agricultural homeopathy, particularly NaM-7CH, PhA-13CH and NaM-31CH treatments, is a viable alternative to optimize the cultivation of species since it increases germination percentage and stimulates initial growth.